Evaluating the performance of Turbo Coding in Optical Communication Systems (Latakia University Journal -Basic Sciences Series, 2020)
In this research, we will study the performance of The Turbo Code in the optical communication systems, because of its advantages in errors’ detection & correction, and as a result improving the performance.We have simulated an optical communication link and studied the effect of its most important factors, where the loss of the fiber had a significant impact on the performance, whether it was due to the fiber length or its damping factor. Then, we have performed a simulation for the Turbo code within that link and studied the effect of its most important factors, the length of the constraint & the inter-leaver and the number of detection times, and compared it with the Block code.We found that it is useful to use The Turbo code in the systems that works at low signal-to-noise ratios, and thus saving on sent capacity as well as reducing link cost.